A Curious case of Vasovagal Shock following Transesophageal Endobronchial Ultrasound-Guided Needle Aspiration (EUS-B-NA) - Niwas, Ram; Shadrach, Benhur Joel; Deokar, Kunal; Dutt, Naveen; Jain, Priyank (Acta Biomedica Atenei Parmensis, 2021)
Esophageal ultrasound-guided bronchoscopic needle aspiration (EUS-B-NA) is a relatively safe procedure with rare complications. A vasovagal attack after EUS-B-NA has not been reported to date. Usually benign and self-limiting, it can cause refractory bradycardia and sudden cardiac arrest. Timely intervention reduces morbidity and mortality. Here, we report a novel case of vasovagal attack after EUS-B-NA and was managed successfully. Management includes identifying the triggering event and keeping the patient in the Trendelenburg position. Atropine is reserved for refractory cases. (www.actabiomedica.it)